2020
DOI: 10.1200/po.20.00158
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Cancer Pain Clinical Features and Differential Opioids Response: A Machine Learning Approach in Patients With Cancer From the IOPS-MS Study

Abstract: PURPOSE A large proportion of patients with cancer suffer from breakthrough cancer pain (BTcP). Several unmet clinical needs concerning BTcP treatment, such as optimal opioid dosages, are being investigated. In this analysis the hypothesis, we explore with an unsupervised learning algorithm whether distinct subtypes of BTcP exist and whether they can provide new insights into clinical practice. METHODS Partitioning around a k-medoids algorithm on a large data set of patients with BTcP, previously collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Patient satisfaction with treatment is an increasingly outcome measure that modulates the pain experience, while assessing the quality and effectiveness of symptom management, especially for BTcP. 11 Although several ancillary analyses of the IOPS-MS study reported descriptive data about patients and pain treatment relationship, 12 , 13 there are some important data worth noting. The findings of this study provided key information regarding the factors influencing the level of satisfaction with BTcP medication.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction with treatment is an increasingly outcome measure that modulates the pain experience, while assessing the quality and effectiveness of symptom management, especially for BTcP. 11 Although several ancillary analyses of the IOPS-MS study reported descriptive data about patients and pain treatment relationship, 12 , 13 there are some important data worth noting. The findings of this study provided key information regarding the factors influencing the level of satisfaction with BTcP medication.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge for BTcP management is the implementation of new procedures that can be useful for both diagnostic and therapeutic approaches. Recently, Pantano et al [19] performed a machine learning approach to identify possible subgroups of both types of BTcP. Their algorithm was based on BTcP therapy satisfaction, clinical features, basal pain, and rapid-onset opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge for BTcP management is the implementation of new procedures that can be useful for both diagnostic and therapeutic approaches. Recently, Pantano et al [9] performed a machine learning approach to identify possible subgroups of both types of BTcP. Their algorithm was based on BTcP therapy satisfaction, clinical features, basal pain, and rapid-onset opioids.…”
Section: Discussionmentioning
confidence: 99%